AN INTRODUCTION TO TEACHING CRIMINOLOGY: RESOURCES AND ISSUES - Brezina, Timothy; Wright, Richard (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Criminology is a complex and disputatious field filled with many theoretical arguments and research approaches that quickly go in and out of style. Staying current with these developments makes teaching criminology challenging, but also exciting and rewarding. Here I review some of the latest resources and issues relating to teaching criminology.I begin by surveying the textbooks and readers, journals, reference works, instructional films, and professional associations that are available to criminology instructors. Some of the latest theoretical, measurement, and justice system controversies and disputes are then discussed. I close with a review of some trends in the teaching of criminology, including the integration of computers, theory, cross-national comparative research, and class, gender, and race issues into these courses.